Satisfaction of the elderly towards subsistence allowance payment in a case study in Chan Yai Sub-district, Kantharalak District, Sisaket Province - Thingsin , Petcharat; Jantanukul, Watcharaporn (Interdisciplinary Academic and Research Journal, 2021)
The objectives of this research (1) were to study the level of satisfaction of the elderly towards the pension payments, and (2) to study the recommendations of the elderly towards the pension payments, which were studied in the district. Chan Yai Subdistrict, Kantharalak District, Sisaket Province. The sample consisted of 310 elderly people in Chan Yai Sub-district who were entitled to receive a living allowance, using random sampling method. Data collection by querying satisfaction data from samples using questionnaires. The statistics used in the data analysis consisted of percentage, mean, and standard deviation, analyzed by software package. The results showed that the satisfaction of the elderly towards the payment of pension as a whole was averaged at the highest level in all 4 aspects. Sorted from highest to lowest average as follows: Registration service, pension disbursement service, pension payment service, and follow-up and evaluation respectively. Recommendations on the pension payments showed that the majority were very satisfied with the pension payments and the performance of the officers. That is to say there is friendliness, there is a follow-up on the rights of the elderly, informing information, there is a system of coordination between community leaders and government agencies and good public relations along the lines of the village, operational procedures. Fast, convenient to receive service including an introduction to operating procedures, clear service procedures Easy to understand and comfortable to receive services from government agencies.